Caring for family with cancer - da Silva Marques Ferreira, Maria de Lourdes [UNESP]; Mutro, Maria Eugênia [UNESP]; Conde, Carla Regiani [UNESP]; Sanches Marin, Maria José; Meneguin, Silmara [UNESP]; Cardoso Mazzetto, Fernanda Moerbeck [UNESP] (Universidad de Concepcion, 2018)
Objective: To understand the experience of family caregivers of patients with cancer. Method: Qualitative study using a phenomenological approach, conducted from January to June 2013 in an Oncological Treatment Unit, based on open interviews with 14 caregivers through the question: “What is your experience in the care of (name)?” Results: Four categories were identified as a result of the caregiver experience: representation of cancer in the family, cancer repercussions on the caregiver’s personal life, facing the repercussion of the denial of the family member’s illness and finitude, and being a caregiver with feelings of gratitude. Conclusions: It was attributed to the role of caregiver a change in routine, with physical and psychological repercussions, and feelings of impotence. The care was also seen as personal satisfaction, and retribution of care to parents. The experience of being a caregiver brings a burden and changes in family structure and the health team can offer formal support and act as a facilitator in this process.
Ser cuidador de familiar con cáncer
Ser cuidador de familiar com câncer
Keywords: Cancer; Family caregiver; Oncology; Oncology nursing